FUNGSI DAN MAKNA BAHASA GAUL DALAM INTERAKSI DIGITAL AKUN TWITTER @TANYARLFESS: KAJIAN SOSIOLINGUISTIK DAN SEMANTIK - Khilyatin Ulinnur; Markhamah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe the form, function, and meaning of slang used in digital interactions on the Twitter account @tanyarlfess. This study uses a qualitative descriptive method with a listening and note-taking technique. Data were analyzed through three stages, namely form analysis (acronyms, foreign language absorption, and phonetic puns), function analysis, and meaning analysis based on literal, connotative, and symbolic categories. The results show that slang on the account emerged through a process of linguistic creativity, such as shortening words, absorbing English terms that have undergone expanded meaning, and phonetic modifications for the sake of expression. Functionally, slang is used as a means of self-expression, forming closeness between users, and marking the identity of the digital generation group. The number of data found was 12 data. In addition, the use of slang also shows the dynamics of meaning that is not only literal, but also contains emotional and symbolic values ​​that represent online communication culture. Thus, slang on social media does not only play a role as a variation of language, but also as a social phenomenon that reflects the interaction patterns, identity, and culture of digital media users.